PENERAPAN PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN MULTIKULTURAL BALI - Katmani, Katmani; Arjiman, Arjiman (Widya Balina, 2025)
As a region with cultural, religious, and ethnic diversity, Bali functions as a social laboratory to understand the interaction between religious communities. The implementation of Islamic Religious Education (PAI) plays a strategic role in building harmony in a multicultural society. Therefore, comprehensive Islamic Religious Education (PAI) is needed to achieve the goal of a harmonious, peaceful, and secure community life even though they have different religions, tribes, nations and even languages. Based on the complexity of the problems above, the focus of the research is: 1) What is the strategy of educators in integrating Islamic values that are relevant to cultural diversity in Bali? 2) What are the challenges faced in implementing PAI in Bali's multicultural environment? 3) What is the PAI curriculum that supports the values of tolerance and diversity? The objectives of this study are: 1) To determine the strategy of educators in integrating Islamic values that are relevant to cultural diversity in Bali. 2) To determine the challenges faced in implementing PAI in Bali's multicultural environment. 3) To determine the PAI curriculum that supports the values of tolerance and diversity. This type of research is qualitative with a descriptive approach, informants are determined purposively. As sources of information (informants) are the Head of the Environment, Head of Customs, Muslim Community Leaders, Head of Foundation, Head of School, students and Parents. Data were collected through interviews, observations and documentation, then analyzed with the stages of data reduction, data presentation and drawing conclusions.